Milestones in Surgery: 60 Years of Open Heart Surgery - Meisner, Hans (The Thoracic and Cardiovascular Surgeon, 2014)
Long periods of experimental research signify the struggle for the goal to substitute the functions of heart and lungs by a machine. In 1931, John Heysham Gibbon, a young surgeon in Boston began animal experiments concentrating on this task. After almost 20 years he succeeded, in May 1953, he performed the first successful open heart operation using a heart–lung machine in the world in Philadelphia. Almost simultaneously, a team of surgeons around Clarence Walton Lillehei in Minneapolis had the same intentions, yet using a different approach. They applied the method of cross-circulation where a parent of the sick child served as “temporary placenta” like a biological oxygenator. Their first successful operation occurred in March 1954. All over the world, many scientists worked intensely on that subject, but did not succeed. However, these two great personalities, persistent and ingenious, reached the same scientific target with very different methods. Thus, both created the foundation for modern cardiac surgery, which is now performed daily all over the world.
Keywords: cardiopulmonary bypass; CPB; congenital heart disease; CHD; history